Effect of Different Watering Regimes on Olive Oil Quality and Composition of Coratina Cultivar Olives Grown on Karst Soil in Croatia - Karolina Brkić Bubola; Šimun Kolega; Šime Marcelić; Zoran Šikić; Ana Gašparović Pinto; Marko Zorica; Dora Klisović; Anja Novoselić; Maja Jukić Špika; Tomislav Kos (Foods, 2022)
Croatian islands are olive growing areas characterized by poor conditions for olive trees because of karst soil and a precipitation deficiency. Under these conditions, irrigation is a very important factor for constant olive oil production. This paper aims to investigate the effects of different watering regimes on quantity, sensory and chemical quality and composition of Coratina cv. olive oil obtained from trees grown on ameliorate karst soil during two harvesting years. Olive trees were subjected to rainfed conditions and three different irrigation treatments (T1—deficit irrigation representing the usual producer’s practice, T2—regulated deficit irrigation in respect to phenological stages, T3—full irrigation). Irrigation treatments increased oil yield compared to rainfed conditions (T1 + 58%, T2 + 66% and T3 + 74%, representing average values for both studied years). All olive oil samples were of extra quality. Irrigation led to a decrease in carotenoids, volatiles, polyunsaturated fatty acids and linolenic acid contents, with no difference found among irrigation treatments. Total phenols and secoiridoids concentration was not affected by irrigation, indicating that similar oil quality could be achieved with less demand on the water supply. Obtained results could help producers to define a suitable irrigation management in particular conditions of ameliorate karst.